Relationship between Nutrient and Phytoplankton Abudance in the Betung Lake, Betung Village, Pangkalan Kuras Districts, Pelalawan Regency, Riau Province - Cindy Fantika Sari; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractMany activities in the Betung Lake contributed organic matter that affect nitrate and phosphate concentration in water and increasing the abudance of phytoplankton. A research aim to know the relationship between nutrien with phytoplankton abudance in the Betung it was conducted in July-August 2019.There were four sampling stations, namely Station I (trees around the station and floating cage), Station II (oil palm plantations, rubber plantations, tourism and residential areas), Station III (floating cage, rubber plantations and residential areas) and Station IV (tourism and oil palm plantations). In each station, there were two sampling points, in the surface (15 cm) and in 2 Secchi depth (160 cm). Sampling were conducted 4 times, once/week. Water quality parameter measured were nitrate, phosphate, phytoplankton abudance, transparency, temperature, pH, depth, dissolved oxygen and free carbondioxide. The result shown: nitrate 0,0229 - 0,0515 mg/L, phosphate 0,0197 - 0,0431 mg/L, phytoplankton abudance 47.232 - 80.640 Cells/L, dissolved oxygen 3,8 - 6,1 mg/L, free carbondioxide 6,2 - 15,53 mg/L, temperature 28,3 - 29,8 °C, transparency 81,5-84,25 cm, pH 5 and depth 195-210 cm. The relationship of nitrate and phosphate with phytoplankton abudance was strong. Equation form of relationship between nutrient with phytoplankton abudance Y = 21235,598 + 1308818,706 X1 – 201135,66 X2andr = 0,71 and R = 0,51.Keywords:Batang Nilo River, Floating Cage, Organic Matter, Water Quality, Mesotrophic